Role of ABA and Gibberellin A3 on gene expression pattern of sugar transporters and invertases in Vitis vinifera cv. Malbec during berry ripening - Murcia, Mauro German; Pontin, Mariela Ana; Piccoli, Patricia Noemí (2018)
Sugars are key constituents that affect quality of grape berries, and consequently the grape metabolic profile relevant to wine’s industry. However, enzymes and transporter genes expression involved in sugar transport at different phenological stages are scarcely studied. In addition, little is known about the role of the plant hormones ABA and Gibberellin (GA3) as endogenous regulators, over the expression pattern of the sugars transporters genes in grapevine. The aim of this study was to analyze the expression pattern of the most relevant sugar transporters and invertases in leaves and berries of grapevine plants cv. Malbec during berry ripening stages and its shift after ABA and GA3 sprays. In leaves, VvHT1 was the sugar transporter highly expressed, whereas VvHT6 was the most abundant in berries throughout berry ripening. Moreover, VvSUC12 and VvSUC27 were expressed at veraison greater in leaves than in berries, suggesting an active phloem loading at the onset of ripening. Applications of ABA and GA3 enhanced the expression of VvSUC12 and VvSUC27 in pre-veraison leaves. Furthermore, hormones increased the expression of VvHT2, VvHT3 and VvHT6 in berries at different stages of ripening favoring sugar unloading from phloem. In conclusion, ABA and GA3 are involved in the long-distance sugar transport from leaves to berries in Vitis vinifera L. cv. Malbec, and their exogenous application could be a suitable strategy to improve the process